Nilai-Nilai Pendidikan dalam Novel "Dua Jempol Untuknya" Karya Alto Makmuralto - Suharto, Asmarani; Djumingin, Sulastriningsih; Saleh, Muhammad (Nuances of Indonesian Language, 2024)
This research aims of explaining and describe the educational values contained in the novel Dua Jempol Untuknya by Alto Makmuralto. The data source for this research is the novel Dua Jempol Untuknya, with data in the form of quoted phrases and sentences containing educational values. The data collection technique used was the note-taking technique. The data analysis technique used is Miles and Huberman's qualitative data analysis technique, namely data reduction, data presentation, and drawing conclusions. The results of the research show that the novel Dua Jempol Untuknya by Alto Makmuralto contains five educational values, namely 1) Divine Education Values, 2) Social Education Values, 3) Moral Education Values, 4) Cultural Education Values, and 5) Educational Values Aesthetics. Based on the research results obtained from these five educational values, it can be concluded that the values found contain a variety of important educational values, which can be used as teaching materials and references in learning to form better and superior personalities for students.